Strategies for Improving the CO2 Adsorption Process of CPO-27-Mg through Thermal Treatment and Urea Functionalization - Godoy, Agustín Alejandro (2023)
In this work, the influence of degassing temperature and urea functionalization were investigated as ways to improve the CO2 adsorption performance of CPO-27-Mg. Through post-synthesis modification treatments, four samples with different degrees of urea functionalization were obtained, incorporating 10, 25, 50, and 100% of urea concerning the metal sites of the MOF. Alternatively, the influence of the degassing temperature of the non-functionalized MOF between 70 and 340 °C was also evaluated. The resulting compounds were characterized by N2 adsorption–desorption isotherms at −196 °C using TGA-MS, FTIR, and PXRD. Finally, the thermally treated and functionalized CPO-27-Mg was evaluated for CO2 capture.